2011
DOI: 10.1029/2010jg001611
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic recovery of foliage after wind disturbance activates ecosystem CO2uptake in cool temperate forests of northern Japan

Abstract: [1] The effects of wind disturbance on forest dynamics and ecosystem CO 2 exchange were examined in cool temperate forests of northern Japan during 2004-2008 using eddy covariance (EC) measurements. One site was a young, even-aged, monoculture, deciduous forest; the other was an uneven-aged mixed forest of evergreen and deciduous overstory tree species, including some over 200 years old. On 8 September 2004, a strong typhoon struck the forests, after which leaf and branch amounts decreased in young growth fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Unlike during extreme drought, the sites' limited ability to sequester carbon was not due to water limitation, but rather a reduction in photosynthesis caused by a loss of leaf area. Repair of the damaged canopy and new growth of leaves will be key for the sites to return to prestorm physiological capacity, but this recovery will be a gradual process, which may take multiple years (Everham & Brokaw, 1996; Gough et al., 2013; Toda et al., 2011). Contrary to a study in mixed forests in Japan, which found higher photosynthetic rates from regrowth of canopy foliage approximately two years after typhoon damage (Toda et al., 2011), the damage at our sites was more extensive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike during extreme drought, the sites' limited ability to sequester carbon was not due to water limitation, but rather a reduction in photosynthesis caused by a loss of leaf area. Repair of the damaged canopy and new growth of leaves will be key for the sites to return to prestorm physiological capacity, but this recovery will be a gradual process, which may take multiple years (Everham & Brokaw, 1996; Gough et al., 2013; Toda et al., 2011). Contrary to a study in mixed forests in Japan, which found higher photosynthetic rates from regrowth of canopy foliage approximately two years after typhoon damage (Toda et al., 2011), the damage at our sites was more extensive.…”
Section: Discussionmentioning
confidence: 99%
“…Repair of the damaged canopy and new growth of leaves will be key for the sites to return to prestorm physiological capacity, but this recovery will be a gradual process, which may take multiple years (Everham & Brokaw, 1996; Gough et al., 2013; Toda et al., 2011). Contrary to a study in mixed forests in Japan, which found higher photosynthetic rates from regrowth of canopy foliage approximately two years after typhoon damage (Toda et al., 2011), the damage at our sites was more extensive. Two years following the storm, we did not observe any large post‐hurricane increases in GEE, except when PAR or air temperature were very high (Figure S3f and S3g in Supporting Information ).…”
Section: Discussionmentioning
confidence: 99%